Modern Ways to Attract and Increase the Efficiency of Investing in Small Businesses - ugli, Davronov Kilichbek Firdavs (European Journal of Life Safety and Stability (2660-9630), 2022)
This article highlights human rights in business and logistics in the context of COVID-19. It was stressed that the rights of workers and specialists should be protected, and people should continue to work without panic.